2011
DOI: 10.3892/or.2011.1237
|View full text |Cite
|
Sign up to set email alerts
|

Vav3 oncogene is involved in regulation of secretory phospholipase A2-IIa expression in prostate cancer

Abstract: Abstract. our previous study revealed that Vav3 oncogene and secretory phospholipase A2-IIa (splA2-IIa) are overexpressed in androgen-independent prostate cancer cells relative to their androgen-dependent counterparts and contribute to development of hormone refractory prostate cancer. Vav3 is a multiple function protein with both signaling molecule and coactivator activities. splA2-IIa is a downstream effector of Her/Her2-pI3K-Akt-nF-κB signaling and involved in inflammatory response and tumorigenesis. The ai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 16 publications
2
2
0
Order By: Relevance
“…IHC analysis showed an elevated expression of sPLA2-IIa in tumor specimens (23,28) (Fig. 3A), confirming the findings of others (19–21).…”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…IHC analysis showed an elevated expression of sPLA2-IIa in tumor specimens (23,28) (Fig. 3A), confirming the findings of others (19–21).…”
Section: Resultssupporting
confidence: 88%
“…We were the first to demonstrate that prostate cancer cells secreted sPLA2-IIa and EGF stimulated sPLA2-IIa expression and secretion via EGFR/HER2-PI3K-Akt-NF-kB signaling (23,28). In the current study, we further explored the underlying mechanism of sPLA2-IIa overexpression and the potential role of sPLA2-IIa in prostate cancer.…”
Section: Introductionmentioning
confidence: 99%
“…We recently reported that elevated signaling of the HER/HER2-PI3K-Akt-NF-kB pathway contributes to sPLA2-IIa overexpression and secretion in prostate cancer cells [17,22,23]. We confirmed that sPLA2-IIa secreted by cancer cells into the circulation to a detecTable level in mice carrying xenograft human tumor.…”
Section: Introductionsupporting
confidence: 76%
“…An increasing body of evidence support the notion that plasma sPLA2-IIa potentially is a novel therapeutic target: i) sPLA2-IIa stimulates tumor cell growth in prostate cancer (20,33,34), colon cancer (35), skin (36), and brain cancer (37,38), while inhibition of eicosanoid signaling leads to cancer regression (39,40); ii) we found that sPLA2-IIa activates HER/HER2-elicited signaling and sPLA2-IIa promoter and stimulates cancer cell growth in a positive feedback manner (20,25,41); iii) sPLA2-IIa stimulates production of vascular endothelial growth factor (VEGF) (42) and nitric oxide synthase expression, contributing to inflammation and angiogenesis in tumors (43,44); iv) sPLA2-IIa abrogates TNF-α-induced apoptosis and compromises immune surveillance function (45); v) sPLA2-IIa stimulates eicosanoid biosynthesis and inflammation contributing to cancer progression (46); vi) through interaction with yet to be identified receptor (18,47), sPLA2-IIa stimulates EGFR-, MAPK-, PI3K/Akt-, NF-κB-mediated cell growth and survival signaling pathways (44,48); and vii) knockdown of secretory phospholipase A2 IIa reduces lung cancer growth both in vitro and in vivo (49). …”
Section: Discussionmentioning
confidence: 85%